The poem “The Heroic triumph of Christ” (Triumphus Christi heroicus) - Maria Golikova (Вестник Православного Свято-Тихоновского гуманитарного университета: Сериа III. Филология, 2025)
The publication presents a translation of the Latin poem "Triumphus Christi heroicus" (The Heroic Triumph of Christ), accompanied by an introductory article and commentary. The work describes Christ's descent into hell after his atoning sacrifice, his victory over Pluto, the pagan god of the underworld, and his minions, as well as his encounter with the dead Old Testament righteous and their deliverance from hell. The authorship of this work remains a matter of debate: for a long time it was attributed to the ancient Roman Christian writer of the 4th century Juvencus. However, Pseudo-Juvencus (another unknown early Christian writer), an anonymous medieval author, and recent studies point to the sixteenth-century German humanist Johann Spangenberg as a possible author. The introductory article analyses the history of the text and hypotheses about the author, and considers the publication history of the Triumph as reconstructed by G. Vredeveld and his theory, which explains why for a long time the authorship was attributed to Juvencus. The artistic features and plot of the poem are examined from the perspective of the Christian literary tradition of the "descent into hell". The main sources in the tradition of texts with the motif of "decens ad infernos", which could have influenced the creation of the text of "Triumph", are given. The mixing of pagan and Christian discourse within one work is separately noted. Three directions of cross-cultural interaction in the text are distinguished: Christian and ancient Roman pagan parallels, ancient Roman realities in Christian interpretation, as well as literary allusions to ancient authors, primarily Ovid and Virgil. "The Heroic Triumph of Christ" is part of the Christian tradition of triumphal Easter hymns, which can be traced from early Christian literary works to Neo-Latin authors. This is the first time this work has been translated into Russian.